Social Media Influencers vs. Brand Ambassador for Brand Image - Almaida, Asty; Nur Baumassepe, A.; Fatima Azzahra, Widi (Opción, 2019)
This study aims to determine the effect of Social Media Influencers and Brand Ambassadors on Brand Image. The data used in this study were obtained from a questionnaire (primary). The sampling method used purposive sam- pling method. The number of samples used was 67 students of the Department of Management, Faculty of Economics and Business, University of Hasanud- din. The analytical method used was descriptive analysis method and mul- tiple linear regression analysis with SPSS 25 application for Windows. The research findings show that Social Media Influencers and Brand Ambassador variables had a positive and significant effect on Brand Image. Compared to Social Media Influencers, the Brand Ambassador variable had a dominant effect on brand image.